2016
DOI: 10.1177/0003319715613923
|View full text |Cite
|
Sign up to set email alerts
|

Utility of γ-Glutamyl Transferase in Predicting Troponin Elevation in Emergency Departments

Abstract: Serum γ-glutamyl transferase (GGT) activity is a risk predictor for the development of coronary artery disease and is related to cardiovascular morbidity and mortality. We evaluated the clinical utility of GGT activity in predicting high troponin levels in patients with acute coronary syndrome (ACS) admitted to the emergency department with chest pain. A total of 200 troponin-positive and 203 troponin-negative patients were classified into groups 1 and 2, respectively. γ-Glutamyl transferase activity was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Quite a few studies also have shown the usefulness of GGT in predicting Troponin elevation in acute coronary syndrome patients. 25,26…”
Section: Discussionmentioning
confidence: 99%
“…Quite a few studies also have shown the usefulness of GGT in predicting Troponin elevation in acute coronary syndrome patients. 25,26…”
Section: Discussionmentioning
confidence: 99%